Dietary supplements for treatment of endometriosis: A review - Yalçın Bahat, Pınar; Ayhan, Işıl; Üreyen Özdemir, Eda; İnceboz, Ümit; Oral, Engin (Acta Biomedica Atenei Parmensis, 2022)
As search for optimal therapy continues for endometriosis, aid of dietary supplements is gaining attention. Supplements can be used for their anti-inflammatory, anti-oxidant, anti-proliferative and immune modulatory charactheristics. We reviewed the literature, evaluated and synthesized effects of vitamin D, zinc, magnesium, omega 3, propolis, quercetin, curcumin, N-acetylcysteine, probiotics, resveratrol, alpha lipoic acid, vitamin C, vitamin E, selenium and epigallocatechin-3-gallate. Based on results of in vitro, animal and human studies, it might be safe to say that dietary supplements can be used as a complementary treatment for endometriosis.